Towards ERM2: managing the relationship between the euro and the other currencies of the European Union - SACCOMANNI, F. (PSL Quarterly Review, 2013)
The Exchange Rate Mechanism 2 (ERM2) framework promises a stronger and closer relationship between the euro and potential non-euro members of the EU. The central factor of the relationship will depend on the progress of the economic convergence of participating countries. ERM2 provides for a suspension of intervention and financing by the European Central Bank (ECB) and non-euro banks during price stabilisation. It clearly indicates an exchange rate objective that is geared towards non-inflationary economic and monetary policies. An examination is undertaken of how best to organise monetary and exchange rate policy cooperation between the euro area and these other EU countries. JEL Codes: F15, E52